Connotative Meanings In The Novel Ghostgirl: Homecoming - Widiani, Ni Made Rita; Beratha, Ni Luh Sutjiati; Putra, I Komang Sumaryana (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study examines the connotative meanings in Tonya Hurley’s novel Ghostgirl: Homecoming, emphasizing the role of language in conveying emotional and cultural nuances in literature. The research underscores the growing importance of connotative analysis in understanding literary expression, particularly in a globalized context where cultural differences influence textual interpretation. The primary objectives are to identify the types of connotative meanings—positive, neutral, and negative—and analyze the messages in the novel’s narrative. Grounded in Leech’s (1981) and Hook’s (1989) theories on connotation, this qualitative study employs a semantic analysis of the novel’s text. Data collection involves documenting and categorizing connotative expressions, followed by a descriptive presentation of findings. The results reveal a predominance of negative connotations, aligning with the novel’s themes of identity, mortality, and self-acceptance. This research enhances readers’ appreciation of Hurley’s narrative craftsmanship and contributes to broader discussions on semantics in literature, highlighting the dynamic interplay between language, emotion, and societal narratives.